Proceso de atención de enfermería en paciente adulto mayor con infarto agudo de miocardio. - Luzarraga Fierro, Melissa Damaris (2023)
Acute myocardial infarction is the cell death of a part of the heart muscle produced by the complete obstruction of the blood supply of the coronary arteries in this way, it is deduced to myocardial infarction as necrosis due to lack of blood supply suddenly. The present case study is about an older adult patient to whom a nursing care process is applied using the observation and interview method, through the management of the clinical history, in addition, pathological antecedents such as obesity and arterial hypertension were identified, added to this; Interventions were carried out aimed at eradicating tissue hypoxia and future complications such as the appearance of tissue necrosis of various organs. For the study, different bibliographic references were consulted that delved into the disease, in this way it was possible to create a theoretical framework with broad definitions, epidemiology, risk factors, diagnosis, prevention and treatment of the disease. Through the study it was possible to meet the objectives set at the beginning of the investigation and provided.